2020
DOI: 10.1002/hpm.3056
|View full text |Cite
|
Sign up to set email alerts
|

Violence in healthcare at a glance: The example of the Turkish physician

Abstract: Background: Violence is an important public health problem that threatens the peace of mind in health institutions as well as in many other sectors. In recent studies, it was stated that violence occurs more frequently in healthcare centers compared to other establishments. In terms of being exposed to violence, healthcare personnel is at 16 times more risk. Violence against healthcare employees has increased gradually in Turkey and the world; it's a serious occupational hazard to consider. Aims: The aim of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The rate was 75% for verbal violence and 7% for physical violence during the pandemic in the current study. Unfortunately, these high rates of violence were similar to the findings of other studies from our country (22,23). The current study also demonstrated that the risk of CF increased in those exposed to violence.…”
Section: Discussionsupporting
confidence: 92%
“…The rate was 75% for verbal violence and 7% for physical violence during the pandemic in the current study. Unfortunately, these high rates of violence were similar to the findings of other studies from our country (22,23). The current study also demonstrated that the risk of CF increased in those exposed to violence.…”
Section: Discussionsupporting
confidence: 92%
“…High rates of violence against physicians have been reported in Turkey (more than 70% of specialty physicians reported some form of violence) [49,50]; in Palestine, on both West Bank and Gaza Strip EDs, especially among younger personnel [51]; in Israel [52]; in Jordan [53]; in Syria [54]; and in Iraq [55,56]. Data showed however, as in other countries, that only 16.4% of assaulted workers reported the violent acts to the authority because of the perception of uselessness and fear of negative consequences [57].…”
Section: Asiamentioning
confidence: 99%
“…A number of recent literatures have reported that physical violence is more prevalent among doctors and varies widely by countries. For example, 5.0% in the UK [ 8 ], 17.11% in Turkey [ 9 ], 19.08% in Syria [ 6 ], and 25. 4% in Pakistan [ 10 ].…”
Section: Introductionmentioning
confidence: 99%